Penggunaan Tiktok Dalam Kampanye Sadar Stunting 2022 Untuk Menurunkan Prevalensi Stunting - Bender, George Wilhelm (LPPM Universitas Bina Sarana Informatika, 2022)
ABSTRACT Indonesia has a big challenge in enjoying the demographic bonus in 2020-2030 where the composition of the population consists of people of productive age reaching twice the non-productive age population due to the high prevalence of stunting. Because stunting is not only a problem of below average height but also slows the development of intelligence, mental retardation, low learning ability, and the risk of diabetes, hypertension and obesity. To reach a quality population of productive age, various efforts have been carried out by the Indonesian government, including through communication activities through the Generation Clean and Healthy (Genbest) in the #SadarStunting campaign. In April 2002 the campaign initiate to use Tiktok along with a target strategy that is more directed at young people as future parents. Tiktok, is the most rapid growth social media with in terms of users in Indonesia, was initially considered a fringe social media because it contains a lot of negative content. However, it has developed into young people favorite and has effectiveness to spread positive messages to young people, including the #SadarStunting 2022 campaign trough Generation Clean and Healthy (Genbest) in spreading the awareness of stunting. The purpose of this study is to describe how the public campaign #SadarStunting 2022 is being carried out by the Directorate General of Public Information and Communication of the Ministry of Communication and Informatics through Generation Clean and Healthy (Genbest) using the social media Tiktok in spreading health messages to the public so they have awareness of stunting. Keyword: social media, tiktok, campaign, stunting